A meaning explanation for HoTT. - Tsementzis, Dimitris (Synthese, 2020)
In the Univalent Foundations of mathematics spatial notions like "point" and "path" are primitive, rather than derived, and all of mathematics is encoded in terms of them. A Homotopy Type Theory is any formal system which realizes this idea. In this paper I will focus on the question of whether a Homotopy Type Theory (as a formalism for the Univalent Foundations) can be justified intuitively as a theory of shapes in the same way that ZFC (as a formalism for set-theoretic foundations) can be justified intuitively as a theory of collections. I first clarify what such an "intuitive justification" should be by distinguishing between formal and pre-formal "meaning explanations" in the vein of Martin-Löf. I then go on to develop a pre-formal meaning explanation for HoTT in terms of primitive spatial notions like "shape", "path" etc.